Impurity-vibrational entropy enables quasi-zero-strain layered oxide cathodes for high-voltage sodium-ion batteries. (1st December 2022) - Ren, Haixia; Zheng, Lumin; Li, Yu; Ni, Qiao; Qian, Ji; Li, Ying; Li, Qiaojun; Liu, Mingquan; Bai, Ying; Weng, Suting; Wang, Xuefeng; Wu, Feng; et al.
Abstract: Layered transition metal oxides based on cationic/anionic redox have gained much attention for high-energy-density sodium ion batteries (SIBs). However, irreversible oxygen activity and unstable crystal structure lead to fast capacity fading and undesired rate performance, limiting its large-scale commercial application. Based on the solid-state physics theory, here we demonstrate that the electrochemical capability in P2-type Na2/3 Ni1/3 Mn2/3 O2 cathode can be significantly improved when impurity-vibrational entropy is increased by simultaneously constructing surface ZrO2 coating and Zr 4+ doping (P2-NaNM@Zr). In-situ and ex-situ X-ray diffraction (XRD) verifies that quasi-zero-strain P2-NaNM@Zr cathode maintains P2 phase structure during the charging/discharging process, achieving an ultra-low volume change (1.18%) upon Na + entire extraction at a high cut-off voltage of 4.5 V. Besides, according to First-principles calculations, we first investigate that the oxygen vacancy formation energy of P2-NaNM@Zr (−2.11 eV) is higher than that of sample P2-NaNM (−2.61 eV), strongly indicating stable and reversible anionic redox reaction. As a result, P2-NaNM@Zr material reveals highly Na storage performance, retaining 86% capacity retention after 1000 cycles at the rate of 5 C within the voltage range of 2.5 − 4.0 V, delivering reversible capacity of 132 mA h g −1 after 50 cycles within 2.0 − 4.5 V. Graphical Abstract: The electrochemical capability in P2-type Na2/3 Ni1/3 Mn2/3 O2 cathode can be significantly improved when impurity-vibrational entropy is increased by simultaneously constructing surface ZrO2 coating and Zr 4+ doping (P2-NaNM@Zr). In-situ XRD verifies that P2-NaNM@Zr cathode achieves an ultra-low volume change (1.18%) upon Na + entire extraction at a high cut-off voltage of 4.5 V. ga1 Highlights: The structure stability and cell capability can be improved by Zr decoration. NaNM@Zr exhibits an ultra-low volume change of 1.18% upon Na + entire extraction. NaNM@Zr has high oxygen vacancy formation energy and stable oxygen redox reaction.